PELATIHAN PEMBUATAN PUPUK MINERAL PLUS DAN CARA PENGGUNAANYA UNTUK MEWUJUDKAN PERTANIAN RAMAH LINGKUNGAN DI KOTA DENPASAR - LANYA, dkk., INDAYATI (Buletin Udayana Mengabdi; Vol 13 No 1 (2014): Vol 13, No 1, April 2014, 2014)
Familier environment agriculture is demanded in global era. Used of overdosage pertilizers both chemical and organic fertilizer affected to pollution and unhealthy agriculture product. In spatial regional planning of Denpasar City number. 27 year 0f 2011 showed that agriculture land in Northern Denpasar City specially in Ubung Kaja village determined as open green space planning. It meant that area should be preserve land and innovation familier environment technology. One of this technology is using of mineral fertilizer plus which is evident in back up familier environment agriculture, healty agriculture product, and increase the quality product and could be preserved open green space planning. Methode of making mineral plus fertilization conducted by lecture, disscusion and exercised. The participant of community service are farmers, head of villages, mosquito surveyor, and staff of Ubung Kaja village. .All of raw material for exerciced has been prepared by Unud service team. The exercised is prior to the teory, lecture of using mineral plus fertilizer, and understand of concept and teor y and continued by interactive disscusion. After that, it was continued with exercised of making mineral plus fertilizer. Unud servised team Unud give example of formulation mineral plus fertilizer. The result of exercised showed that most of participants (> 80%) understand to make mineral plus fertilizer and knowing to the utilization mineral plus fertilization why it was not destroy the soil and increase quality of agriculture product. The participant could formulated raw material of mineral plus fertilizer. This is showed in disscusion and enthusiastic practice in making of mineral plus fertilizer. Key words: trining , mineral plus fertilizer, enveromental famers, product quality